A resin scintillator and its preparation method and application in radiation detector
By mixing epoxy resin with GOS ceramic powder and promoting stacking densification by using mechanical and ultrasound methods, the problems of complex and high cost of traditional scintillator preparation processes are solved, and a low-cost resin scintillator suitable for industrial security is prepared. It realizes efficient radiation detection performance and stable radiation resistance.
Patent Information
- Application Number
- CN202411230378.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-04
AI Technical Summary
The preparation process of traditional GOS ceramic scintillators is complex and costly, and it is difficult to meet the needs of low-cost and efficient scintillator materials in the industrial security field.
Epoxy resin is used to mix with GOS scintillation ceramic powders of different particle sizes, and the accumulation and density of ceramic powders is promoted through mechanical force, ultrasonic oscillation and centrifugal acceleration fields, and cross-linking and curing through dehydration and condensation reaction to prepare resin scintillation. Reduces production costs and energy consumption.
The prepared resin scintillator has high bulk density, excellent light output performance and good radiation resistance. It is suitable for X-ray detectors in the industrial security field, significantly reducing production and processing costs, and is easy to process and cut.
Smart Images

Figure CN118732011B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of radiation measurement and scintillation detectors, and in particular relates to a resin scintillator and a preparation method thereof and application in radiation detectors. Background Art
[0002] As an important radiation detection material, scintillators are widely used in nuclear medicine, safety inspection, particle physics research, industrial flaw detection and other fields. Their basic function is to emit visible light after absorbing high-energy particles or X-rays. This light signal is then captured by photomultiplier tubes or other optical sensors to detect and measure radiation. The performance of scintillator materials directly affects the response speed, energy resolution and sensitivity of the detector.
[0003] Traditional scintillator materials are mostly inorganic crystals, such as sodium iodide (NaI), cesium iodide (CsI), gadolinium oxysulfide (GOS), etc. Among them, GOS scintillator ceramics have been widely used in medical imaging (such as computed tomography CT), industrial safety testing and other fields due to their excellent physical and chemical properties, such as low afterglow time, high light output and good radiation resistance. However, the preparation process of GOS ceramic scintillator is relatively complicated, and usually requires the use of expensive equipment such as hot pressing furnaces or hot isostatic pressing furnaces, which not only increases the manufacturing cost, but also consumes a lot of energy.
[0004] For some application scenarios, such as industrial security, although the light output performance requirements of the scintillator are not high, cost control is an important consideration. Therefore, developing a scintillator material with lower cost, simple preparation process and stable performance is of great practical significance for promoting the development and progress of industrial security technology. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a resin scintillator and a preparation method thereof and application in a radiation detector, the main purpose of which is to meet the radiation detection performance while effectively reducing the cost so as to promote its actual application.
[0006] The first aspect of the present invention is to provide a method for preparing a resin scintillator, comprising the following steps: mixing a resin mixture containing an epoxy resin and an anhydride compound with GOS scintillating ceramic powders of different particle sizes to obtain a scintillating resin mixed slurry; applying a mechanical force to the scintillating resin mixed slurry to promote the stacking and densification of the GOS scintillating ceramic powders in the scintillating resin mixed slurry; cross-linking and curing the scintillating resin mixed slurry through a dehydration condensation reaction of the anhydride groups and the epoxy groups in the resin mixture to obtain a resin scintillator.
[0007] The types of epoxy resins include but are not limited to bisphenol A epoxy resin, bisphenol F epoxy resin, aliphatic glycidyl ether epoxy resin, alicyclic epoxy resin, glycidyl ester epoxy resin, silicone modified epoxy resin, and polyurethane.
[0008] Among them, the GOS scintillating ceramic powder includes GOS ceramic powder within a first particle size range and GOS ceramic powder within a second particle size range; the first particle size range is 20±1μm, and the second particle size range is 10±1μm; the mass ratio of the GOS ceramic powder within the first particle size range to the GOS ceramic powder within the second particle size range is in the range of 74:26~78:22.
[0009] As a further optimization scheme for the preparation method of resin scintillator, the scintillating resin mixed slurry is placed in a composite field containing an ultrasonic oscillation field and a centrifugal acceleration field to promote the compaction of GOS scintillating ceramic powder.
[0010] As a further optimization scheme for the preparation method of the resin scintillator, in the resin mixture, the epoxy resin uses E-73 alicyclic epoxy resin, the acid anhydride compound uses methyl hexahydrophthalic anhydride, and also includes a curing catalyst N,N-dimethylbenzylamine; the resin mixture is cross-linked and cured by heating.
[0011] As a further optimization scheme for the preparation method of the resin scintillator, defoaming agent ethylene glycol is also added into the resin mixture.
[0012] As a further optimization scheme for the preparation method of the resin scintillator, the following steps are included: the epoxy resin, the acid anhydride, the curing catalyst and the defoaming agent are first mixed uniformly to obtain a transparent liquid; the transparent liquid and the premixed uniformly GOS scintillating ceramic powders of different particle sizes are then added into a vacuum glue mixer, and mixed until they are in a uniform state under vacuum conditions; then the mixture is transferred into a silica gel container of an ultrasonic centrifugal heating device, and centrifugally rotated while ultrasonically dispersing, and the heating program is turned on to uniformly heat the temperature to 80°C and keep the temperature for 2 hours, then cool the temperature to room temperature, and the ultrasound and centrifugation are turned off after the temperature reaches 80°C and is maintained for 1 hour.
[0013] The second aspect of the present invention is to provide a resin scintillator, including an epoxy resin package formed by curing and GOS scintillating ceramic powders of different particle sizes densely deposited in the epoxy resin package; the first particle size range of the GOS scintillating ceramic powder is 20±5μm, the second particle size range is 10±5μm, and the mass ratio of the GOS ceramic powder within the first particle size range to the GOS ceramic powder within the second particle size range is in the range of 66:34~88:12; the density of the resin scintillator is not less than 4.8 g / cm³.
[0014] As a further optimization scheme for the resin scintillator, an epoxy resin encapsulation body is formed by cross-linking and curing E-73 alicyclic epoxy resin and methyl hexahydrophthalic anhydride under the catalysis of N,N-dimethylbenzylamine.
[0015] As a further optimization solution for the resin scintillator, the resin scintillator is prepared according to the above method.
[0016] The resin scintillator provided in the second aspect of the present invention is preferably used in an X-ray detector in the field of industrial security. Specifically, the resin scintillator is processed into scintillator blocks of a preset size, which are arranged in a straight line to form a one-dimensional linear array structure. The surface of each scintillator block is encapsulated with a reflective material, and only one side of the light-emitting surface is retained. A photodiode is coupled to the light-emitting surface of each scintillator block; the scintillator block generates visible light after being excited by X-rays, and the photodiode generates an electrical signal after receiving the visible light.
[0017] Beneficial Effects
[0018] The present invention disperses two different GOS powders with specific particle sizes in epoxy resin in a specific ratio, and simultaneously applies ultrasound and centrifugal action to prepare a resin scintillator with high packing density and high light output performance.
[0019] The method of the present invention can produce a resin scintillator with a low epoxy resin content, effectively reducing the proportion of yellowed epoxy resin produced after radiation damage, significantly improving the radiation resistance of the resin scintillator, and making its application in a radiation environment more stable and reliable.
[0020] The method of the present invention does not rely on high-cost and high-energy consumption hot pressing furnaces and hot isostatic pressing furnaces. This production method not only reduces production costs, but also reduces negative impacts on the environment.
[0021] Compared with scintillation crystals, the resin scintillator prepared by the present invention has lower hardness and is not easy to crack, which makes it easier to process and cut. Users can process it into various shapes as needed, with lower processing costs, and it can meet the application requirements of different types of radiation detection devices.
[0022] The resin scintillator of the present invention has excellent radiation detection performance and low production and processing costs, and has significant advantages over scintillating crystals when used in X-ray detectors in the field of industrial security. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a raw material ratio diagram for Examples 1 to 16.
[0024] Figure 2 This is a physical picture of the block-shaped finished product obtained after demoulding.
[0025] Figure 3Actual pictures of resin scintillating materials cut into different shapes and sizes.
[0026] Figure 4 It is a test result diagram of Example 1 to Example 16.
[0027] Figure 5 Schematic diagram of the close packing of powder particles of two different particle sizes.
[0028] Figure 6 This is a raw material ratio diagram for Example 2-1 to Example 2-6.
[0029] Figure 7 It is a graph of the test results of Example 2-1 to Example 2-6. DETAILED DESCRIPTION
[0030] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0031] Example 1
[0032] Step 1: Press Figure 1 Weigh GOS ceramic powder of corresponding particle size according to the mass ratio recorded in the mixing tank, use a roller mixer at a speed of 600 rpm to mix for 10 minutes, and take it out for use.
[0033] Step 2: Add 50 parts of E-73 epoxy resin, 40 parts of methylhexahydrophthalic anhydride, 0.1 parts of N,N-dimethylbenzylamine, and 0.05 parts of ethylene glycol into the vacuum mixer tank, mix at 2000 rpm for 3 minutes until it becomes a uniform transparent liquid, then pour into another container for later use.
[0034] Step 3: Weigh 300 g of the GOS ceramic powder obtained in step 1 and add it together with 200 g of E-73 epoxy resin obtained in step 2 into a vacuum mixer, and mix at 2000 rpm for 5 minutes to obtain a liquid scintillating resin.
[0035] Step 4: Add liquid scintillation resin into the silicone mold, place it in a constant temperature oven, heat it to 80°C at a rate of 5°C / min, and keep it warm for 3 hours.
[0036] Step 5: After the heat preservation is completed, the temperature is lowered to room temperature at a rate of 2°C / min, and the solidified scintillation resin is peeled off from the silicone mold to obtain the finished product.
[0037] Step 6: The finished product is taken out and processed into the desired shape.
[0038] Example 2
[0039] Step 1: Press Figure 1Weigh GOS ceramic powder of corresponding particle size according to the mass ratio recorded in the mixing tank, use a roller mixer at a speed of 600 rpm to mix for 10 minutes, and take it out for use.
[0040] Step 2: Add 50 parts of E-73 epoxy resin, 40 parts of methylhexahydrophthalic anhydride, 0.1 parts of N,N-dimethylbenzylamine, and 0.05 parts of ethylene glycol into the vacuum mixer tank, mix at 2000 rpm for 3 minutes until it becomes a uniform transparent liquid, then pour into another container for later use.
[0041] Step 3: Weigh 300 g of the GOS ceramic powder obtained in step 1 and add it together with 200 g of E-73 epoxy resin obtained in step 2 into a vacuum mixer, and mix at 2000 rpm for 5 minutes to obtain a liquid scintillating resin.
[0042] Step 4: Add liquid scintillation resin into the silicone mold, put it into the centrifugal ultrasound machine, turn on the ultrasound module and centrifugal rotation, and heat it to 80°C at a rate of 5°C / min, and keep it warm for 2 hours; turn off the ultrasound module and centrifugal rotation after reaching 80°C for 1 hour.
[0043] Step 5: After the heat preservation is completed, the temperature is lowered to room temperature at a rate of 2°C / min, and the solidified scintillation resin is peeled off from the silicone mold to obtain the finished product.
[0044] Step 6: The finished product is taken out and processed into the desired shape.
[0045] Embodiment 3 to Embodiment 15
[0046] Compared with Example 2, Examples 3 to 15 are only Figure 1 The formula of Example 2 was used to weigh GOS ceramic powders with different particle size combinations and ratios, and the other operating steps were consistent with those in Example 2.
[0047] Example 16
[0048] Take the GOS scintillating ceramic block and process it into the desired shape.
[0049] The block-shaped finished product obtained after demoulding in step 5 of the embodiment is as follows Figure 2 As shown, the block products obtained in different embodiments have similar appearances. The lower white opaque area is the area filled with GOS ceramic powder, which can be used to be processed into glittering parts of different shapes, and the upper transparent area is the unfilled resin area. The block products obtained in different embodiments only show different thicknesses in the lower filled area and the upper unfilled area. Figure 2 The middle block (a) is the block-shaped finished product obtained in step 5 of Example 2. Figure 2 The middle block (b) is the block-shaped finished product obtained in step 5 of Example 2. Figure 2The middle block (c) is the block-shaped finished product obtained in step 5 of Example 6.
[0050] According to the requirements of different usage scenarios or test requirements, the block-shaped finished product obtained in step 5 of the embodiment can be cut into samples of different shapes and sizes, for example Figure 3 The long strip samples shown in S1.1 to S1.4 and S2.1 to S2.4, Figure 3 Rectangular sheet samples shown in S3 and S4.
[0051] In order to verify the technical effects of various embodiments of the present invention, the following tests were performed:
[0052] Test sample preparation
[0053] Sample specifications: The scintillating materials obtained in each embodiment are selected and processed into a standard test specification size, namely 40 mm×8 mm×0.35 mm, without an additional reflective layer on the sample surface.
[0054] Sample quantity: For each example, 10 test specimens of the same specification were prepared, and the test data were averaged and the corresponding decimal places were retained to obtain the average performance data.
[0055] Irradiation test conditions
[0056] X-ray source parameters: A 120 kV, 10 mA X-ray source was used, and the sample-to-detector distance (SID) was set to 25 cm.
[0057] Radiation source conditions: Use 60 Co radiation source, irradiation intensity of 10000 Gy / h, continuous irradiation time of 1 hour.
[0058] Index measurement
[0059] Sample density: Before irradiation, the density of each test sample (unit: g / cm³) was measured and recorded to evaluate the density of the GOS ceramic in the test sample.
[0060] Relative light output: The light output of each sample under irradiation was measured by a photomultiplier tube and the average value of 10 samples was calculated to quantitatively evaluate the scintillation performance.
[0061] Comparison after irradiation: Compare the performance changes of samples before and after irradiation, and calculate the ratio of light output after irradiation to light output before irradiation to evaluate the stability and radiation tolerance of the material.
[0062] Test Results
[0063] Test results such as Figure 4As shown, in the sample preparation process of Example 1, only ordinary heating curing was performed without using an ultrasonic centrifugal device to increase the packing density. Compared with the sample of Example 2 with the same composition but subjected to ultrasonic centrifugal densification, the density and relative light output were poor, and the radiation resistance stability also had a significant difference.
[0064] The sample of Example 2 uses 75% of 20μm GOS powder and 25% of 10μm GOS powder as the scintillation source. Compared with the sample of Example 2, the samples of Example 3 and Example 4 replace part of the 10μm GOS powder with 5μm GOS powder with a smaller particle size during the preparation process. The results show that such an adjustment leads to a significant decrease in the density, light output performance and radiation resistance of the sample.
[0065] In the sample preparation process of Examples 5 to 7, only two kinds of GOS powders with large particle sizes were used, namely, 15 μm GOS powder and 20 μm GOS powder, and the ratio of the two powders was adjusted. It was found that when two kinds of GOS powders with large particle sizes were used, no matter how the ratio of the two powders was adjusted, excellent compactness, light output performance and radiation resistance performance could not be achieved.
[0066] In the sample preparation process of Examples 8 to 11, only two kinds of small-particle-size GOS powders were used, namely, 5μm GOS powder and 10μm GOS powder, and the ratio of the two powders was adjusted. It was found that when two small-particle-size GOS powders were used, no matter how the ratio of the two was adjusted, good compactness, light output performance and radiation resistance could not be achieved, and the performance of the samples prepared by combining 15μm GOS powder and 20μm GOS powder was generally worse.
[0067] In the sample preparation process of Examples 12 to 14, 15 μm GOS powder was used as the main scintillation source, and two small-particle GOS powders were used as auxiliary scintillation sources, and the ratio of the two auxiliary scintillation source powders was adjusted. It was found that in this case, no matter how the ratio of 10 μm and 5 μm GOS powders was adjusted, excellent compactness, light output performance and radiation resistance performance could not be achieved. Among them, although Example 13 has excellent radiation resistance stability, it still has a significant gap with Example 2 in terms of compactness and light output performance.
[0068] The above experimental results show that there is a relatively obvious positive correlation between the light output performance and the compactness of the sample; the correlation between the radiation resistance stability and the compactness of the sample is relatively weak, and there is a large degree of uncertainty. In order to improve the compactness of the sample, Example 15 is based on Figure 5The close packing method shown approximates the particle size and weight ratio of the two GOS powder particles, but after testing, it was found that the samples prepared in this way showed poor density, light output performance and radiation resistance, indicating that the density and light output performance of the samples do not only depend on the spatial size effect of the powder particles.
[0069] Based on Example 2, GOS powder was further formulated. The particle size and formulation of GOS powder in each sample were Figure 6 shown.
[0070] The samples prepared in Examples 2-1 to 2-6 were tested using the same test method. The results are as follows: Figure 7 Each sample prepared from Example 2-1 to Example 2-6 has a viscosity exceeding 4.8 g / cm 3 density, and exhibits excellent light output performance and radiation resistance.
[0071] The above embodiments are exemplary, and their purpose is to illustrate the technical concept and features of the present invention so that people familiar with the technology in this field can understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a resin scintillator, characterized in that: The following steps are involved: A resin mixture containing epoxy resin and anhydride compound is mixed with GOS scintillating ceramic powders of different particle sizes to obtain a scintillating resin mixed slurry; Applying mechanical coercive force to the scintillating resin mixed slurry to promote the packing and densification of the GOS scintillating ceramic powder in the scintillating resin mixed slurry; The anhydride groups and epoxy groups in the resin mixture cross-link and solidify the scintillating resin mixed slurry through a dehydration condensation reaction to obtain the resin scintillator; The GOS scintillating ceramic powder includes GOS ceramic powder within a first particle size range and GOS ceramic powder within a second particle size range; the first particle size range is 20±1 μm, and the second particle size range is 10±1 μm; the mass ratio of the GOS ceramic powder within the first particle size range to the GOS ceramic powder within the second particle size range is in the range of 74:26~78:
22.
2. The method for preparing a resin scintillator according to claim 1, characterized in that: The scintillating resin mixed slurry is placed in a composite field containing an ultrasonic oscillation field and a centrifugal acceleration field, so that the GOS scintillating ceramic powder is compacted and stacked.
3. The method for preparing a resin scintillator according to claim 1, characterized in that: In the resin mixture, the epoxy resin is E-73 alicyclic epoxy resin, the acid anhydride compound is methyl hexahydrophthalic anhydride, and the curing catalyst N,N-dimethylbenzylamine is also included; the resin mixture is cross-linked and cured by heating.
4. The method for preparing a resin scintillator according to claim 3, characterized in that: The resin mixture is also added with defoaming agent ethylene glycol.
5. The method for preparing a resin scintillator according to claim 4, characterized in that: The following steps are involved: The epoxy resin, the acid anhydride compound, the curing catalyst and the defoaming agent are first mixed uniformly to obtain a transparent liquid; then the transparent liquid and the premixed uniform GOS scintillating ceramic powders of different particle sizes are added into a vacuum glue mixer, and mixed until they are in a uniform state under vacuum conditions; then the mixture is transferred into a silica gel container of an ultrasonic centrifugal heating device, and centrifugally rotated while ultrasonically dispersing, and the heating program is turned on to uniformly heat the temperature to 80°C and keep the temperature for 2 hours, then cool the temperature to room temperature, and the ultrasound and centrifugation are turned off after the temperature reaches 80°C and is maintained for 1 hour.
6. A resin scintillator, characterized in that: It comprises a cured epoxy resin package and GOS scintillating ceramic powders of different particle sizes densely deposited in the epoxy resin package; the GOS scintillating ceramic powders comprise GOS ceramic powders within a first particle size range and GOS ceramic powders within a second particle size range; the first particle size range is 20±1μm, and the second particle size range is 10±1μm; the mass ratio of the GOS ceramic powders within the first particle size range to the GOS ceramic powders within the second particle size range is within the range of 66:34~88:12; the density of the resin scintillator is not less than 4.8 g / cm³.
7. The resin scintillator according to claim 6, characterized in that: The epoxy resin encapsulation body is formed by cross-linking and curing E-73 alicyclic epoxy resin and methyl hexahydrophthalic anhydride under the catalytic action of N,N-dimethylbenzylamine.
8. The resin scintillator according to claim 6, characterized in that: The resin scintillator is prepared according to the method according to any one of claims 1 to 5.
9. Use of the resin scintillator according to any one of claims 6 to 8 in a radiation detector, characterized in that: The resin scintillator is used for X-ray detectors in the field of industrial security.
10. The use of the resin scintillator in a radiation detector according to claim 9, characterized in that: The resin scintillator is processed into scintillator blocks of preset sizes, which are arranged in a straight line to form a one-dimensional linear array structure. The surface of each scintillator block is encapsulated with reflective material, leaving only one side of the light-emitting surface. A photodiode is coupled to the light-emitting surface of each scintillator block. The scintillator block generates visible light after being excited by X-rays, and the photodiode generates an electrical signal after receiving the visible light.
Citation Information
Patent Citations
Preparation method and application of gadolinium oxysulfide scintillation ceramic
CN114031403A
Scintillator structure and method for producing same
CN116904183A
Scintillator structure
CN117121120A
Scintillator structure and scintillator evaluation method
CN117625190A
GOS scintillator using polymer, and fabricating method thereof
KR1020140132099A